2011
DOI: 10.1016/j.vaccine.2011.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Stability of RNA virus attenuation approaches

Abstract: The greatest risk from live-attenuated vaccines is reversion to virulence. Particular concerns arise for RNA viruses, which exhibit high mutation frequencies. We examined the stability of 3 attenuation strategies for the alphavirus, Venezuelan equine encephalitis virus (VEEV): a traditional, point mutation-dependent attenuation approach exemplified by TC-83; a rationally designed, targeted-mutation approach represented by V3526; and a chimeric vaccine, SIN/TC/ ZPC. Our findings suggest that the chimeric strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Several alternative strategies based on directed manipulation of the alphaviral genome, such as chimeras consisting of two distinct alphaviruses or internal ribosome entry site-dependent translation of structural proteins, have proven to produce stably attenuated, safe, and effective strains in recent studies (17,28,32,51,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Several alternative strategies based on directed manipulation of the alphaviral genome, such as chimeras consisting of two distinct alphaviruses or internal ribosome entry site-dependent translation of structural proteins, have proven to produce stably attenuated, safe, and effective strains in recent studies (17,28,32,51,53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, DNA shuffling has been mainly used to generate chimeric viruses with novel tissue tropism or with broader antigenic representation (5-7). To our knowledge, attenuation of a virus by DNA shuffling has never been done, although virus attenuation by constructing chimeric viruses, which is very different from the DNA-shuffling strategy used in this study, has been reported (8).…”
mentioning
confidence: 96%
“…However, the vaccine causes adverse effects such as headache and fever in approximately 23% of vaccine recipients, while another approximately 18% of recipients do not develop sufficient neutralizing antibody titers [79]. Reversion mutations can explain adverse effects that have been observed with live-attenuated vaccines including TC-83 [80]. Nevertheless, due to its long history of clinical use, the TC-83 represents a logical starting point for proof-of-concept studies, as well as for preparation of improved vaccines against VEEV [80].…”
Section: Dna-launched Vaccines For Alphavirusesmentioning
confidence: 99%